Effects of polyunsaturated fatty acids on hepatic lipid metabolism - Kassem, Mohamad Ali (Al-Mukhtar Journal of Sciences, 2008)
Effects of dietary treatment of male albino rats with eicosapentaenoic acid (EPA) or docosahexaenoic acid (DHA) on hepatic mitochondrial lipid metabolism have been investigated. Mitochondria isolated from rats given these treatments were shown to have increased ability to respire on acyl-CoA esters in the presence of malonate. In rats treated with EPA in the fed state, the amount of EPA incorporated into mitochondrial lipids wase markedly more increased as compared to control rats. A hypolipidaemic effect of dietry EPA was only observed when the fatty acid was given to fed rats, may result from diminished synthesis and export of very-low density lipoprotein from the liver.In line with this argument the hepatic level of triacylglycerol was found not be increased in these rats, and this may therefore reflect increased hepatic B-oxidation. Diminished lipolysis may also occur, as dietary EPA can inhibit lipolysis in mice. Rats treated with EPA in the fasted state, in contrast, exhibited hypoglycaemia. When malonate in the incubations was replaced with malate, mitochondria from treated animals were found to exhibit diminished rates of respiration on polyunsaturated acyl-CoA esters. This phenomenon could not attributed to changes in activity of carnitine palmitoyltransferase1. No significant differences between the effects of EPA and DHA.